THE DISPOSITION OF SPECIAL POST-WAR RESERVES AT THE CLOSE OF WORLD WAR II. - Mead, Stuart B. (The Accounting Review, 1952)
The article discusses the disposition of special post-war reserves at the close of World War II. In the article, interest was centered primarily in only one of several types of reserves. What 134 large manufacturing corporations did with the special reserve created to cover post-war reconversion costs has been shown. In recent years there has been some criticism of methods and motives used in the creation of reserves, especially those set up for contingencies. Accountants are beginning to suggest that, because earned surplus is itself available for contingencies, there is no reason for creating a contingency reserve. While there was no need for the unused reserves and those created as a matter of conservatism, the post-war reserves that were used properly would not be subject to the above criticism. The purpose of the post-war reserve is quite different from that of contingency reserves. The purpose of the post-war reserve is the proper assignment of costs to periodic revenue. If costs are assigned properly to periodic revenue, there will be less distortion of annual income. A reserve created for such a purpose and used properly, is undoubtedly a necessary accounting procedure.